The impact of educational interventions on COVID-19 and vaccination attitudes among patients in Michigan: A prospective study - Takagi, Maya Asami; Hess, Samantha; Smith, Zachary; Gawronski, Karissa; Kumar, Ayushi; Horsley, Jacob; Haddad, Nicholas; Noveloso, Bernard; Zyzanski, Stephen; Ragina, Neli (Frontiers in Public Health, 2023)
Background Mass vaccination serves as an effective strategy to combat the COVID-19 pandemic. Vaccine hesitancy is a recognized impediment to achieving a vaccination rate necessary to protect communities. However, solutions and interventions to address this issue are limited by a lack of prior research. Methods Over 200 patients from 18 Michigan counties participated in this study. Each participant received an initial survey, including demographical questions and knowledge and opinion questions regarding COVID-19 and vaccines. Participants were randomly assigned an educational intervention in either video or infographic format. Patients received a post-survey to assess changes in knowledge and attitudes. Paired sample t-tests and ANOVA were used to measure the effectiveness of the educational interventions. Participants also elected to complete a 3-month follow-up survey. Results Patients showed increased knowledge after the educational intervention in six out of seven COVID-19 topics (p < 0.005). There was increased vaccine acceptance after the intervention but no difference in the effectiveness between the two intervention modalities. Post-intervention, more patients believed in CDC recommendations (p = 0.005), trusted the vaccine (p = 0.001), believed the vaccines had adequate testing (p = 0.019), recognized prior mistreatment in the medical care system (p = 0.005), agreed that a source they trust told them to receive a vaccine (p = 0.015), and were worried about taking time off of work to get a vaccine (p = 0.023). Additionally, post-intervention, patients were less concerned about mild reactions of the virus (p = 0.005), the rapid development of the vaccines (p < 0.001), and vaccine side effects (p = 0.031). Data demonstrated that attitude and knowledge improved when comparing pre-educational intervention to follow-up but decreased from post-intervention to follow-up. Conclusion The findings illustrate that educational interventions improved COVID-19 and vaccine knowledge among patients and that the knowledge was retained. Educational interventions serve as powerful tools to increase knowledge within communities and address negative views on vaccination. Interventions should be continually utilized to reinforce information within communities to improve vaccination rates.